Black carbon and mineral dust on two glaciers on the central Tibetan Plateau: sources and implications. Issue 256 (10th April 2020) - Li, Xiaofei; Kang, Shichang; Sprenger, Michael; Zhang, Yulan; He, Xiaobo; Zhang, Guoshuai; Tripathee, Lekhendra; Li, Chaoliu; Cao, Junji
Abstract: Sources and implications of black carbon (BC) and mineral dust (MD) on two glaciers on the central Tibetan Plateau were estimated based on in situ measurements and modeling. The results indicated that BC and MD accounted for ~11 ± 1% and 4 ± 0% of the albedo reduction relative to clean snow, while the radiative forcing varied between 11 and 196 and 1–89 W m −2, respectively. Assessment of BC and MD contributions to the glacier melt can reach up 88 to 434 and 35 to 187 mm w.e., respectively, contributing ~9–23 and 4–10% of the total glacier melt. A footprint analysis indicated that BC and MD deposited on the glaciers originated mainly from the Middle East, Central Asia, North China and South Asia during the study period. Moreover, a potentially large fraction of BC may have originated from local and regional fossil fuel combustion. This study suggests that BC and MD will enhance glacier melt and provides a scientific basis for regional mitigation efforts.